Convective and shear‐induced turbulence in the deep Kane Gap. Issue 11 (5th November 2013) - van, Hans; Morozov, Eugene; Gostiaux, Louis; Tarakanov, Roman
<x xml:space="preserve">Abstract</x> [1] The boundary layer above a 4569 m deep slope in the near‐equatorial N‐Atlantic Ocean Kane Gap, a throughflow for Antarctic Bottom Water (AABW), is characterized by two distinct turbulent regimes that differ by an order of magnitude in intensity depending on the direction of throughflow. During southward and downward flow, vertical mixing is vigorous. This is inferred from high‐resolution temperature observations between 6 and 132 m above the bottom. For a representative case study of 2 days, average values are found for dissipation rate of ε = 2.1 ± 1 × 10−9 W kg−1 and eddy diffusivity of Kz = 7 ± 4 × 10−4 m2 s−1. The mixing is across relatively large vertical overturns. During northward and upward flow, smaller overturns are more horizontal as in stratified shear flow (with representative 2 day mean ε = 6 ± 3 × 10−11 W kg−1, Kz = 4 ± 2 × 10−5 m2 s−1). Stratification is approximately the same during both flow directions. Although the different turbulence regimes are partially associated with frictional boundary layers of large‐scale flows above sloping topography, but not with those over flat bottoms, and partially with flow across a hill‐promontory, internal waves are a dominant process in promoting turbulence. In addition, internal waves are observed to push stratification toward the bottom thereby importantly contributing to the mixing of AABW.